Characterization of Ficus benjamina and Artocarpus heterophyllus Proteases as Potential Rennet Alternatives - Sukmana, Andreas Binar Aji; Widyaningrum, Indy; Lani, Rischa Karmila; Kasmiyati, Sri (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2020)
Rennet, a milk coagulant exhibiting proteolytic activity, is a crucial component in cheese industries. Its price and availability have discouraged the growth of some small scale cheese industries. Therefore, an alternative for rennet will be beneficial for the industries. Among other sources, plant proteases offer some advantages as rennet alternatives. This study aimed to investigate the potential of plant proteases obtained from the latex as potential rennet alternatives. A total of six plants from the genus Ficus and Artocarpus were screened for their proteolytic activity and milk coagulating ability. The screening indicated that all six tested plants displayed proteolytic activity at various levels, but only Ficus benjamina and Artocarpus heterophyllus produced a firm milk curd. Hence, both F. benjamina and A. heterophyllus were determined to be the most potential. Further characterizations suggested that F. benjamina and A. heterophyllus protease were optimum at pH 7.0 also at 50°C and 40°C, respectively. At their optimum conditions, both proteases exhibited a lower MCA/PA ratio than that of the rennet. This study contributed to scientific knowledge development by becoming the first to characterize the optimum conditions of F. benjamina and A. heterophyllus’ proteases, investigate their MCA/PA ratio, and compare their activity against commercial rennet. The examination of their potentials as rennet alternatives could benefit small cheese industries and the communities.